2015
DOI: 10.1002/ijc.29508
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in cervical intraepithelial neoplasia in young women inBritishColumbia after introduction of theHPVvaccine: An ecological analysis

Abstract: We report on the rates of cervical intraepithelial neoplasia (CIN) in young women aged 15-22 years of age in British Columbia before and after the introduction of an HPV vaccine program. Rates of cervical intraepithelial neoplasia (CIN) 21 for each age stratum (15)(16)(17)(18)(19)(20)(21)(22) in the calendar years 2004-2012 for the province of British Columbia were obtained from the BC Cancer Agency's population-based cervical cancer program. Incidence rate ratios (IRR) of CIN21 were described and compared bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 21 publications
4
36
0
2
Order By: Relevance
“…The study observed a significant decrease in the incidence of high-grade abnormalities in young girls younger (< 18 years) after implementing the HPV vaccination program in Australia. A Canadian study ­conducted by Ogilvie et al [55] achieved similar results. The study reported the rates of CIN in young women (aged 15–22 years) living in British Columbia before and after the introduction of an HPV vaccine program (in 2007).…”
Section: Data From Real Worldsupporting
confidence: 71%
“…The study observed a significant decrease in the incidence of high-grade abnormalities in young girls younger (< 18 years) after implementing the HPV vaccination program in Australia. A Canadian study ­conducted by Ogilvie et al [55] achieved similar results. The study reported the rates of CIN in young women (aged 15–22 years) living in British Columbia before and after the introduction of an HPV vaccine program (in 2007).…”
Section: Data From Real Worldsupporting
confidence: 71%
“…The early protection offered by the vaccine at the population level against vaccine-targeted HPV infections, genital warts and cervical premalignant lesions has been reported from countries that introduced the vaccine between 2007 and 20104849505152535455. In Denmark, the atypia or worse and CIN2 or worse lesions increased in all age groups during 2000-2010, the incidence of such lesions decreased significantly in women younger than 18 yr [estimated annual percentage change (EAPC) - 33.4%; 95% CI -49.6; -12.0] and in 18-20 yr old women (EAPC - 12.6%; 95% CI -19.3; -5.3), after the introduction of HPV vaccination programme; however, no significant decrease was seen in older age groups50.…”
Section: Effectiveness Of Hpv Vaccine In the National Immunization Prmentioning
confidence: 99%
“…Epidemiological studies from Australia, Canada, UK and the US demonstrate population level reductions in the rates of HPV, GW, and cervical cancer lesions after introduction of HPV vaccine programs for girls [611]. With strong empirical evidence for both vaccine safety and efficacy [5], the HPV vaccine is an important innovation in cancer prevention [6, 12]. …”
Section: Introductionmentioning
confidence: 99%